Novel Synthesis of Thiopyrimidine Compounds from Dibenzo-18-Crown-6 and Evaluation of Antibacterial Activity - Zena Abdali; Raheem Jameel Mahesein (Academia Open, 2024)
In this study, we present a novel synthesis approach for the production of thiopyrimidine compounds, including P-OH-Thiopyrimidine, P-NO2-Thiopyrimidine, and P-Cl2-Thiopyrimidine, from the precursor compound dibenzo-18-crown-6 (DB-18-CE-6). These thiopyrimidine compounds have shown significant potential for various applications, particularly as antibacterial agents. The synthesis involved the reaction of DB-18-CE-6-derived alpha-beta unsaturated ketones with thiourea in a basic medium, resulting in successful cyclization. The synthesized thiopyrimidine compounds were evaluated for their antibacterial activity against common bacterial strains, including Streptococcus, Staphylococcus, and Proteus, and compared to the antibiotic Azithromycin. The results demonstrated that the thiopyrimidine compounds (Z, Z1, Z2, Z3) exhibited excellent antibacterial activity, surpassing Azithromycin, and highlighting their potential as effective alternatives to combat bacterial infections. This research opens new avenues for the development of antibacterial agents and emphasizes the significance of thiopyrimidine compounds in addressing bacterial resistance issues. Highlights : Novel synthesis of thiopyrimidine compounds from DB-18-CE-6. Evaluation of antibacterial activity against Streptococcus, Staphylococcus, and Proteus. Potential of thiopyrimidine compounds as effective antibacterial agents. Keywords : Thiopyrimidine compounds, Antibacterial activity, DB-18-CE-6, Novel synthesis, Bacterial resistance.